Discordance of PD-L1 status between primary and metastatic breast cancer: A systematic review and meta-analysis. (September 2021) - Boman, Caroline; Zerdes, Ioannis; Mårtensson, Kira; Bergh, Jonas; Foukakis, Theodoros; Valachis, Antonios; Matikas, Alexios
Highlights: This is a systematic review and meta-analysis of PD-L1 expression in breast cancer. PD-L1 expression rates were higher in primary tumors than in metastases. Discordance of PD-L1 expression was more common in immune than tumor cells. Discordance between PD-L1 status in primary tumor and metastasis was bi-directional. These results highlight the need to obtain metastatic biopsies. Abstract: Introduction: Programmed cell death ligand 1 (PD-L1) expression is predictive for benefit from immunotherapy in several human malignancies including triple negative breast cancer. Lower positivity rates but a larger relative benefit from atezolizumab has been implied when PD-L1 status is assessed at metastatic sites. We aimed to study the discordance of PD-L1 expression between primary tumor and metastasis in breast cancer due to its potential clinical utility. Methods: Cochrane Library, Embase, Medline and Web of science were searched for studies reporting on PD-L1 expression in primary and metastatic breast cancer, followed by data extraction. Outcomes included pooled PD-L1 positivity rates in tumor cells, immune cells or both in primary tumor and metastasis, PD-L1 discordance between matched primary tumors and metastasis and direction of discordance. Results: Of 2552 identified entries following de-duplication, 20 studies fulfilled the predefined inclusion criteria. Pooled PD-L1 positivity rate was higher in primary tumors compared to metastasis when assessed in immune cells (51.2% vs 37.1% p < 0.001) and tumor/immune cells (30.1% vs 14.6% p < 0.001), but not in tumor cells (18.7% vs 17.8% p = 0.65). PD-L1 positivity was lowest when assessed in bone metastases (12%) and highest in lymph nodes (60%). Discordance between primary tumors and metastasis was bidirectional, with higher pooled discordance rates when PD-L1 expression was assessed in immune compared to tumor cells (39.5% vs 13.6%, p < 0.001). Conclusion: The observed considerable discordance between PD-L1 status in primary and metastatic breast cancer emphasizes the importance of appropriate tissue sampling when selecting patients for immunotherapy.